P482Tyrosine phosphorylation is important in Hic-5 subcellular localisation in Src -/- mouse embryonic fibroblasts. (15th July 2014) - Pieri, M; Ohanian, J; Ohanian, V
Abstract: Purpose: The actin cytoskeleton is a dynamic structure regulated by actin regulatory proteins, an example of which is Hic-5 (hydrogen peroxide-inducible clone 5). Hic-5 is an adaptor protein regulated by tyrosine phosphorylation, which has been shown to affect cytoskeletal organisation in rat mesenteric small arteries and fibroblasts, but the cellular mechanisms involved are unclear. The aims of this study were to analyse Hic-5 tyrosine phosphorylation and determine its effect on Hic-5 subcellular localisation in Src null mouse embryonic fibroblasts (Src -/- MEFs), which were used as a model system for further work that will be carried out in rat vascular smooth muscle cells. Methods: Src -/- MEFs were transfected with yellow fluorescent protein (YFP)-tagged Hic-5 or Y60F-Hic-5 (a mutant form of Hic-5 in which Tyr-60 has been mutated to phenylalanine) ± v-Src. Following transfections, wild type and mutant Hic-5 were purified by GFP-trap, and tyrosine phosphorylation was analysed by western blotting and mass spectrometry. Localisation of wild type and mutant Hic-5 in the presence and absence of v-Src in Src -/- MEFs was determined by immunofluorescence. Results: There was minimal tyrosine phosphorylation of Y60F-Hic-5-YFP compared to wild type Hic-5-YFP in Src -/- MEFs in the presence of v-Src (p≤0.05, n=3). Tyrosine-60 was identified as a phosphorylated residue using mass spectrometry. Importantly, immunofluorescence experiments have shown wild type Hic-5-YFP being relocalised from the cytoplasm to focal adhesions of these cells in the presence of v-Src, whereas Y60F-Hic-5-YFP remained mostly in the cytoplasm under the same conditions. Conclusion: Hic-5 phosphorylation on Tyr-60 is Src-dependent and is important in determining subcellular localisation of Hic-5 in Src -/- MEFs. Taking into consideration that Hic-5 has been previously shown to be tyrosine-phosphorylated in response to noradrenaline in rat mesenteric small arteries with associated remodelling of the actin cytoskeleton, our results have implications for the importance of Hic-5 tyrosine phosphorylation in focal adhesion signalling in vascular smooth muscle cells.